(untitled) (Journal of Naval Architecture and Marine Engineering, 2023)
This article introduces the development of an unmanned remotely operated vehicle (ROV) that measures 35 cm x 26 cm x 23 cm and weighs 1.59 kg. The primary objective is to remotely communicate in real time using serial protocol to record the vehicle’s orientation data. The three DC motors powering the ROV are controlled by a multi-parameter root-locus proportional integral (MRPL-PI) controller. Utilizing the processing capabilities of the Atmega328 microcontroller, heading, depth control, and water condition monitoring are all accomplished simultaneously. The Arduino development environment is used to establish the ROV’s remote control. The problem with human divers who can only descend to a depth of 30 meters is resolved by the proposed ROV’s ability to dive up to 100 meters underwater. Furthermore, the suggested vehicle can be beneficial in marine applications such as measurement, maintenance, operations, and surveillance.